EFEKTIVITAS DAUN BANGUN-BANGUN DALAM MENINGKATKAN PRODUKSI ASI PADA IBU NIFAS - Kumala Sari Rambe; Dede Maysarah (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
Exclusive breastfeeding is breastfeeding for the first 6 months of the baby's life without the intake of other food or drinks except vitamins, drugs and ORS. Bangun-bangun plant (Coleus Amboinus Lour) is one of the types of plants consumed by new mothers in North Sumatra, especially by the Batak tribe. The purpose of this study was to determine the effectiveness of the leaves of Bangun-bangun in increasing milk production in the Independent Practice of Midwife Rismayani Harahap, S.Tr.Keb. The research method uses the Quasi Experiment Design method using the Non-Equevalent Control group approach. The study used the Independent T-Test test, namely P = 0.000, which means that there is an Effectiveness of Giving Bangun-bangun Leaves to Increase Breast Milk Production in Postpartum Mothers